Conserved high activity binding peptides are involved in adhesion of two detergent-resistant membrane-associated merozoite proteins to red blood cells during invasion (2010)
Detergent resistant membranes (DRMs) of Plasmodium falciparum merozoites contain a large number of glycosylphosphatidylinositol (GPI)-anchored proteins that have been implicated in interactions between merozoites and red blood cells (RBCs). In this study, two cysteine-rich proteins anchored by GPI to merozoite DRMs (Pf92 and Pf113) were studied with the aim of identifying regions actively involved in RBC invasion. By means of binding assays, high-activity binding peptides (HABPs) with a large number of binding sites per RBC were identified in Pf92 and Pf113. The nature of the RBC surface receptors for these HABPs was explored using enzyme-treated RBCs and cross-linking assays. Invasion inhibition and immunofluorescence localization studies suggest that Pf92 and Pf113 are involved in RBC invasion and that their adhesion to RBCs is mediated by such HABPs. Additionally, polymorphism and circular dichroism studies support their inclusion in further studies to design components of an antimalarial vaccine. © 2010 American Chemical Society.